Faktor-Faktor Yang Berhubungan Dengan Kejadian BBLR di Wilayah Puskesmas Martapura 1 Tahun 2024 - Eka Radiani; Erni Yuliastuti; Megawati Megawati; Nur Rohmah Prihatanti (Jurnal Kesehatan Indonesia, 2024)
Low Birth Weight (LBW) is a health issue that contributes to infant mortality rates. The incidence of LBW at Martapura 1 Public Health Center in 2023 was 126 cases, and from January to June 2024, there were 67 cases. To determine the factors associated with the incidence of LBW in the Martapura 1 Public Health Center area.This study is an analytical study with a case-control research design. The population consists of all mothers who gave birth from January to June 2024, totaling 665 individuals. The research sample consists of 134 mothers, with 67 mothers who gave birth to LBW infants as the case group and 67 mothers who did not as the control group, maintaining a 1:1 case-to-control ratio. It can be concluded that: (a) there is a relationship between the age of the mother giving birth and the incidence of LBW in the Martapura 1 Health Center Area in 2024; (b) there is a relationship between the parity of the mother giving birth and the incidence of LBW in the Martapura 1 Health Center Area in 2024; and (c) there is a relationship between the nutritional status of the mother giving birth and the incidence of LBW in the Martapura 1 Health Center Area in 2024.